Medical pluralism and rationalities for HIV care utilization among discordant couples in Siaya County, rural western Kenya. (August 2019) - Arego, Judy; Ondenge, Ken; Odero, Isdorah; Awuonda, Eucabeth; Omoro, Tereza; Akelo, Victor; Mudhune, Victor; Gust, Deborah A
Understanding healthcare seeking and utilization of members of discordant couples can help in implementing effective HIV treatment, care, and support. We conducted a qualitative study comprised of in-depth interviews (n = 26) and ten focus group discussions (n = 73) with community members including opinion leaders, healthcare workers, and members of discordant couples. A portion of the latter group had been participants in the HIV Prevention Trials Network (HPTN) 052 study. Themes that emerged from the data were pragmatism and the realities of hospital care, quest for a cure through traditional medicine, and religious dogma. Medical pluralism is practiced by members of discordant couples seeking HIV care through intersections of hospital facility services and traditional and religious therapeutic options. It would be prudent for healthcare policy makers and conventional medical providers to recognize the importance of traditional medicine and religion in the lives of members of HIV discordant couples and make efforts to integrate the positive concepts of both into the couples' overall health plan.